Tip Apex Distance As Predictor of Mechanical Complications in Unstable Intertrochanteric Fractures Treated with Proximal Femoral Nails - Rasheed, Muhammad Asif; Amin, Muhammad Suhail; Chaudhry, Muhammad Nadeem; Haseeb, Malik Muhammad; Muhammad junaid; Naz, Kashif Ali (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the significance of Tip Apex Distance (TAD) as a predictor of mechanical complications in unstableintertrochanteric fractures treated with proximal femoral nails and to ascertain a cut-off TAD value for maintaining stableconstructs.Study Design: Cross-sectional analytical study.Place and Duration of Study: Department of Orthopedics, Combined Military Hospital, Rawalpindi Pakistan, from Oct 2021 toAug 2023.Methodology: We assessed patient records for reduction categorized as per baumgartner’s and Chang’s criteria. Weevaluated post operative radiographs for TAD and loss of reduction. We reviewed radiological follow ups at 3 months and 6months to identify mechanical complications. We determined the statistical significance of TAD (p<0.05) and used receiveroperating characteristic (ROC) curve to find the sensitive and specific cut-off value for TAD regarding mechanicalcomplications.Results: Among 132 patients, 12(9.09%) experienced mechanical complications. The mean age was 76.3±7.98 years, with105 males (79.5%) and 27 females (20.5%). The mean TAD was 24.56±2.76 mm, and the mean calcar gap was 5.16±1.27mm. We found a TAD cut-off of 24.5 mm to be 66.7% sensitive and 51.7% specific for predicting mechanical complications(AUC 0.55). Complications were significant in Cleveland zones: center-center (40.9%), inferior center (49.2%), and inferiorposterior (9.9%) (p<0.001). The mean time to full weight-bearing without support was 21.00±1.22 weeks.Conclusion: Maintaining a TAD of less than 25 mm when using the helical blade of intramedullary fixation devices isrecommended. TAD is not an independent sole predictor of mechanical complications.